(3caGjI GdJYdje aj eYQag hVY GdJbhjes - (3Gdche GdQjTj , CMeO Hf ZdGe Gddg Hf CMeO Hf eMeO, TgGH GdOjf,J (B836 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLg (B: (3agPg ebOeg dWjag VefJgG fcJG TQjag JTJed Ydi eYQag GSJNQGL GdJbhje s
(3BNQgG (B:s
(3hWdhY GdTYQi hZjQ Pdc hdjcf gPG BNQ eG CQOfGg ef gPg GdLedg s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B192 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B39s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B127 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B88 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs